2020
DOI: 10.3390/info11090456
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Question-Answering System for Natural Disaster Domains Based on Social Media Messages Posted at the Time of Disaster

Abstract: Natural disasters are events that humans cannot control, and Japan has suffered from many such disasters over its long history. Many of these have caused severe damage to human lives and property. These days, numerous Japanese people have gained considerable experience preparing for disasters and are now striving to predict the effects of disasters using social network services (SNSs) to exchange information in real time. Currently, Twitter is the most popular and powerful SNS tool used for disaster response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Kemavuthanon and Uchida [53], in their paper "Integrated question-answering system for natural-disaster domains based on social-media messages posted at the time of disaster", concluded that there is a possibility of creating a support system for foreigners residing in Japan to assist them in obtaining necessary real-time information during disasters in the future.…”
Section: Natural Disasters Big Data and Social Mediamentioning
confidence: 99%
“…Kemavuthanon and Uchida [53], in their paper "Integrated question-answering system for natural-disaster domains based on social-media messages posted at the time of disaster", concluded that there is a possibility of creating a support system for foreigners residing in Japan to assist them in obtaining necessary real-time information during disasters in the future.…”
Section: Natural Disasters Big Data and Social Mediamentioning
confidence: 99%